Development and psychometric validation of a self-administered questionnaire assessing the acceptance of influenza vaccination: the Vaccinees' Perception of Injection (VAPI©) questionnaire - Dias-Barbosa Carla; Viala-Danten Muriel; Chevat Catherine; Nguyen Van (Health and Quality of Life Outcomes, 2009)
Abstract Background Influenza is among the most common infectious diseases. The main protection against influenza is vaccination. A self-administered questionnaire was developed and validated for use in clinical trials to assess subjects' perception and acceptance of influenza vaccination and its subsequent injection site reactions (ISR). Methods The VAPI questionnaire was developed based on interviews with vaccinees. The initial version was administered to subjects in international clinical trials comparing intradermal with intramuscular influenza vaccination. Item reduction and scale construction were carried out using principal component and multitrait analyses (n = 549). Psychometric validation of the final version was conducted per country (n = 5,543) and included construct and clinical validity and internal consistency reliability. All subjects gave their written informed consent before being interviewed or included in the clinical studies. Results The final questionnaire comprised 4 dimensions ("bother from ISR"; "arm movement"; "sleep"; "acceptability") grouping 16 items, and 5 individual items (anxiety before vaccination; bother from pain during vaccination; satisfaction with injection system; willingness to be vaccinated next year; anxiety about vaccination next year). Construct validity was confirmed for all scales in most of the countries. Internal consistency reliability was good for all versions (Cronbach's alpha ranging from 0.68 to 0.94), as was clinical validity: scores were positively correlated with the severity of ISR and pain. Conclusion The VAPI questionnaire is a valid and reliable tool, assessing the acceptance of vaccine injection and reactions following vaccination. Trial registration NCT00258934, NCT00383526, NCT00383539.